Gyrosigma xiamenense sp. nov. (Bacillariophyta) from the middle intertidal zone, Xiamen Bay, southern China - Liu, Bing; Sterrenburg, F.a.s.; Huang, Bangqin (Phytotaxa, 2015)
Gyrosigma xiamenense sp. nov., a new diatom species from the middle intertidal zone, Xiamen Bay, southern China, was studied by light and scanning electron microscopy. The valves are large and sigmoid, with parallel sides. The raphe sternum has single curvature. Externally, a row of round pores is present on the mantle; isomorphic proximal raphe fissures turn first in opposite directions, then both final parts of the fissures run nearly parallel to the longitudinal striae. Internally, a row of areolae closest to the raphe sternum is capped by small projections on the primary side whilst these are absent on the secondary side; proximal raphe endings are first club-shaped, then the final parts of the two raphe endings form two T-shaped slits being separated from the club-shaped part by a tiny bridge; there is a vermiform bar in the middle of the raphe nodule. G. xiamenense is epipelic and lives in marine habitats.